Bioequivalence for a Fixed‐Dose Combination Formulation of Bazedoxifene and Cholecalciferol Compared With the Corresponding Single Entities Given Together. Issue 8 (30th June 2021) - Yun, Jae Nam; Kan, Hye‐Su; Yeun, Ji‐Sun; Kim, Jae‐Hoon; Lee, Minyu; Kim, Namsick; Oh, Tae‐Young; Nam, Seung‐Kwan; Choi, Yoon Seok; Kwon, In Sun; Hoe, Kwang Lae; Hong, Jang Hee
Abstract: A fixed‐dose combination (FDC) formulation of bazedoxifene 20 mg and cholecalciferol 8 mg was developed to increase medication compliance and convenience for osteoporosis patients. This study was conducted to demonstrate bioequivalence by comparing the pharmacokinetic (PK) profiles and tolerability of an FDC tablet and the individual component tablets. A randomized, open‐label, single‐dosing, 2‐treatment, 2‐period, 2‐sequence crossover study was conducted in 52 healthy subjects. All subjects were randomly assigned to 2 sequences, and they received FDC tablets of bazedoxifene and cholecalciferol and individual component tablets. Serial blood samples for PK evaluation were collected up to 24 hours predose and 120 hours postdose, and the PK parameters were estimated by noncompartmental methods. Throughout the study, tolerability was assessed based on adverse events, vital signs, and clinical laboratory tests. Of the enrolled 52 subjects, 47 subjects completed the study. The results, the geometric mean ratios (GMRs) and 90% confidence intervals (90%CIs), of bazedoxifene Cmax and AUC0‐t for FDC to single entities given together were 0.98 (0.91‐1.05) and 1.02 (0.97‐1.07), respectively. The GMRs (90%CIs) of cholecalciferol Cmax and AUC0‐t for FDC to single entities given together were 0.96 (0.91‐1.00) and 0.94 (0.90‐0.99), respectively. Overall, the GMRs (90%CIs) of the PK parameter of bazedoxifene and cholecalciferol fell within the conventional bioequivalence range of 0.8‐1.25. There were no clinically significant differences in the safety profile between the 2 treatments. In conclusion, this study confirmed the development of a new FDC drug by demonstrating that the FDC formulation of bazedoxifene and cholecalciferol is biologically equivalent to the coadministered individual formulations.